Polak Mazurowi wilkiem. Czy "Róża" Wojciecha Smarzowskiego jest filmem antypolskim? [Pole is a Wolf to a Mazur. Is "Róża" by Wojciech Smarzowski an Anti-Polish Film?] - Weiher-Sitkiewicz, Krystyna (Panoptikum, 2016)
The author of this article tries to explain why the controversial film "Róża" by Wojciech Smarzowski was well received by the wright-wing media which recognized other historical films from this period, such as Ida by Pawel Pawlikowski and "Aftermath" by Wladyslaw Pasikowski, as anti-Polish and even harmful. The author examines three aspects of the film: whether it is actually anti-Polish, anti-Soviet or maybe pro-German. At the end she reveals the director’s strategy which allowed to avoid the dispute over the misinterpretation of historical events.
https://katalog.adlr.link/Record/ai-53-428753